Assessing The Validity of The Going Concern in The Financial Reports of Listed Companies During The COVID-19 Pandemic and The Conflict in Ukraine on The Example of Companies in The Construction Industry - Magdalena GLEBOCKA; Ewa MACKOWIAK (Communications of International Proceedings, 2022)
The paper is focused on the assessing the validity of the going concern statements during the Covid 19 pandemic and war in Ukraine. Difficult time in the economy, supply chain disruptions, pandemic lock downs and quarantine absences together with rising risks caused by  the Ukraine war make it more and more important for stakeholders to receive an appropriate information from enterprises’ managements.  The study was performed based on information provided in annual financial statements of 15 construction companies listed on Warsaw Stock Exchange.  Analysis shows companies and their management have different sensitivity during the risk analysis. Despite generally the same conditions the risk assessment differs between companies even if all are active in the same sector. It shows the importance of the application of common rules for risk assessment and going concern statements in order to ensure reliable information is provided to stakeholders.
Keywords: business community; assessment of resource impairment; risk analysis; financial statements